Stratégies pour une approche culturelle des géosciences et sa mise en valeur touristique - Boureboune, L (Journal of Human Sciences, 2021)
Tourist activities are more and more frequently directed by initiatives concerning the cultural landscape. Cultural assets inserted in an integrated cultural landscape can be either natural or resulting from man’s activities, which are archeological, historical, architectural … The geomorphological and geological assets produce a high attractivity by their spectacular features. These features produce a good value in their cultural aspects in scientific, educational or geodiversity type. In an integrated cultural landscape the relationships between geosciences and cultural assets of the archaeological and historical architectural type can be considered according the three approaches: the environmental, the historical and the cultural approach.